Технологические условия повышения точности механической обработки отверстий - Новиков, Федор Васильевич; Полянский, Владимир Иванович; Дитиненко, Станислав Александрович (НТУ "ХПИ", 2016)
Аналитически обоснованы условия повышения точности механической обработки отверстия в случае его несоосности с осевым многолезвийным инструментом с учетом упругого перемещения, возникающего в технологической системе. Показано, что увеличение количества лезвий осевого многолезвийного инструмента не позволяет уменьшить упругое перемещение и погрешность обработки отверстия. Целесообразно использовать развертки с разнонаклонными зубьями, снижающие интенсивность колебаний и повышающие точность обработки путем исключения работы "по следу".

Improving the accuracy of machining of holes is an urgent task of modern engineering. This appli es in particular to the manufacture of high-precision holes in parts of hydraulic equipment, and other products. Currently, practical experience gained great precision machining of holes, in particular with modern methods abrading. Currently, practical experience gained great precision machining of holes, in particular with modern methods abrading. Analytically grounded process conditions increase the accuracy of machining holes in the case of axial misalignment multiblade tool based on the magnitude of the elastic movement occurring in the process system. It is shown that increasing the number of blades of the axial multiblade tool actually does not affect the value of the maximum elastic movements. It was also found that the error of the axial hole machining multiblade tools with inclined blades is the same as in the processing of the axial hole multiblade tools with straight blades. Therefore it is difficult to reduce the hole machining accuracy by increasing the number of multiple tip tool blades. It is advisable to use the scanner with teeth that reduce the intensity of the vibrations and improve machining accuracy by eliminating the work "on the trail". Errors of processing in this case will be determined by the elastic movements arising in technologycal system.
Technological conditions of improvement of precision machining of holes
Keywords: отверстия; механическая обработка; точность; осевой многолезвийный инструмент; упругое перемещение; погрешность обработки; разнонаклонные зубья; развертки; machining of holes; precision machining; elastic movement; error handling